2018
DOI: 10.3390/ma11091540
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Flow-Casting Production of Bioactive Glass Coatings on Porous Titanium for Bone Tissue Engineering

Abstract: Additive manufacturing enabled the fabrication of porous titanium (PT) with customized porosity and mechanical properties. However, functionalization of PT surfaces with bioactive coatings is being challenged due to sophisticated geometry and highly porous structure. In this study, a facile flow-casting technique was developed to produce homogeneous 45S5 bioactive glass (BG) coatings on the entire surface of PT. The coating weight as a function of BG concentration in a BG-PVA slurry was investigated to achieve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 43 publications
(43 reference statements)
0
6
0
Order By: Relevance
“…Bioceramic coatings, like sphene-based (CaTiSiO 5 ) coatings, can promote early cell/implant surface interactions and osteoblast proliferation and differentiation due to Ca and Si dissolution from the sphene coating [ 17 , 18 ]. In addition, bioactive glasses are used as bioactive coatings for bone scaffolds [ 19 ] and for porous titanium implants [ 20 ]. Coatings based on the organic bone phase are also used for improving implant/bone responses [ 1 , 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Bioceramic coatings, like sphene-based (CaTiSiO 5 ) coatings, can promote early cell/implant surface interactions and osteoblast proliferation and differentiation due to Ca and Si dissolution from the sphene coating [ 17 , 18 ]. In addition, bioactive glasses are used as bioactive coatings for bone scaffolds [ 19 ] and for porous titanium implants [ 20 ]. Coatings based on the organic bone phase are also used for improving implant/bone responses [ 1 , 2 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Considering the fact that the pore size and strut size of 3D-printed porous Ti6Al4V scaffolds were in the range of hundreds of micrometers whereas the thickness of the PSC coating was merely several micrometers, PSC coating would not significantly change the mechanical properties except bioactivity. H. Yang et al 35 also found that Mesoporous Bioactive Glass coating did not markedly change the compressive strength of the original 3D-printed porous Ti6Al4V scaffolds. pH of PSC dissolutions.…”
Section: Characterization Of the Psc And Psc Coatingmentioning
confidence: 96%
“…With further developments in additive manufacturing technology, preparation techniques such as DLP ( Schmidleithner et al, 2019 ), SLM ( Yang et al, 2018 ; Pei et al, 2020 ), or EBM ( Nune et al, 2017a ; Zhang et al, 2020 ) have been gradually applied to bioengineered porous bone tissue materials, benefiting from the high-precision material formation of light-cured materials or powder materials by high-precision light sources or energy beams. In this context, the most typical and widely used technology is SLM, which mainly uses a micron laser beam to melt the micron powder material with high precision.…”
Section: Definition Of Pore Structure Dimensionmentioning
confidence: 99%